Bacteriocin, Antimicrobial as A New Natural Food Preservative: Its Potential and Challenges - Sri Surati (Badan Pengawas Obat dan Makanan, 2020)
Improving food safety and quality remains a major challenge in worldwide. Modern society tends to choose the foods that are fresh tasting, free of chemical additives, rich in nutrients and has been introduced to minimally processed. Bacteriocins as new natural preservatives could be produced by Gram-positive bacteria and Gram-negative bacteria, even though it is mostly originated from Lactic Acid Bacteria (LAB). Bacteriocin-producing bacteria as well as bacteriocin has long been used in some countries as alternatives to replace chemical additives. The use of these antimicrobial agents has been proven effective in food manufacturing and distribution chain, especially in increasing shelf life of food products. Other potential from the use of bio-preservatives in various types of food is still huge. However, approval of bio-preservatives and their commercially applications is still limited. This study will review the selection criteria for bacteria used, the mechanism of action, its potential application in the food and pharmaceutical industries and its potential as an anti-cancer agent. In addition, this study will explore the main challenges faced including its stability and the possible risk of resistance to microorganisms. This review will also describe a series of processes for identification, characterization, and approval of the use of bacteriocins before they are commercially marketed. In addition, the safety issue of using bacteriocin-producing bacteria, especially as probiotics, also needs to be considered as a fundamental for quality control and the improvement of drug and food safety.